ASSOCIATION OF ACID REFLUX AND LARYNGOMALACIA : A COMPREHENSIVE SYSTEMATIC REVIEW - Primadhiya Sentani, Maynanda; Ferrial Nugraha, Ramadhani (Journal of Advanced Research in Medical and Health Science (ISSN 2208-2425), 2024)
Background: Laryngomalacia (LM) is a common cause of stridor in infants and young children. It is characterized by reflux episodes that are slightly acidic, which harm the supraglottic tissues and exacerbate airway collapse. Further investigation is required to ascertain the presence of the gastric proteolytic enzyme pepsin in the oral secretions of patients with less severe LM, as it has been proposed as a biomarker for both weakly acidic and nonacid reflux events. Methods: This systematic review focused on full-text English literature published between 2014 and 2024, adhering to PRISMA 2020 principles. Without a DOI, editorials and review papers that were published in the same journal as the submission were not accepted. ScienceDirect, PubMed, and SagePub were only a few of the web resources used to compile the literature. Result: Following a thorough screening process consisting of three stages, six papers were determined to have pertinent connections to our ongoing comprehensive investigation. Following that, the text as a whole was thoroughly studied and these sections received more attention. Conclusion: Recent research has revealed a link between laryngomalacia (LM) and pepsin, a diagnostic marker, but no significant differences have been found. Pepsin is a common comorbidity in LM patients and serves as a biomarker for airway reflux, but its harmful impact on proximal airways remains unclear.